Hubungan Tinggi Dan Lama Pemakaian High Heels Dengan Nyeri Punggung Bawah Pada Pramugari Maskapai X - Almayda, Reza; Bachtiar, Farahdina; Prabowo, Eko; Purnamadyawati, Purnamadyawati (Jurnal Fisioterapi Terapan Indonesia, 2022)
Low back pain is discomfort in the lower back area in the form of a feeling of pain and discomfort. A flight attendant is a profession that uses high heels when working. The use of high heels can cause changes in the fulcrum of the body when walking. Problems occur when wearing high heels for a long time, causing the lumbar muscles to shorten and lower back pain to occur. The purpose of this study was to determine the correlation between the height of the heels and the length of use of high heels with complaints of low back pain in the flight attendants of X Airlines. The parameter used to measure complaints of low back pain is NRS. This research is a correlation study with a cross-sectional approach. Based on the results of statistical tests using SPSS, it was obtained that the p-value = 0.001. Thus, there is a correlation between low back pain complaints with flying hours in 24 hours and the working period. This study did not find a correlation between the height of the heels with complaints of low back pain (p> 0.05).